HIV Treatment Outcomes Among Patients Initiated on Antiretroviral Therapy Pre and Post-Universal Test and Treat Guidelines in South Africa - Hirasen K; Fox MP; Hendrickson CJ; Sineke T; Onoya D (Dove Medical Press, 2020)
Kamban Hirasen, 1 Matthew P Fox, 1–3 Cheryl J Hendrickson, 1 Tembeka Sineke, 1 Dorina Onoya 1 1Health Economics and Epidemiology Research Office, Department of Internal Medicine, School of Clinical Medicine, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, South Africa; 2Department of Global Health, Boston University School of Public Health, Boston, MA, USA; 3Department of Epidemiology, Boston University School of Public Health, Boston, MA, USACorrespondence: Dorina OnoyaHealth Economics and Epidemiology Research Office, 39 Empire Road, Empire Park, Parktown, Johannesburg 2193, South AfricaTel +27 010 001 7936Email donoya@heroza.orgIntroduction: Officially rolled out on 01 September 2016, South Africa’s Universal Test and Treat (UTT) policy calls for first-line antiretroviral treatment (ART) initiation among all known HIV-positive patients, irrespective of CD4 cell count. We evaluate treatment outcomes of patients initiated on first-line ART directly before and after the implementation of UTT.Methods: We analysed prospectively collected clinical cohort data among ART-naïve adult patients within two HIV clinics in Johannesburg, South Africa. We compare two groups: 1) an unexposed pre-UTT group initiating treatment from 01 December 2014 to 31 May 2015; and 2) an exposed UTT group initiating treatment from 01 December 2016 to 31 May 2017. Primary treatment outcomes included lost to follow-up (LTFU) (> 90 days late for the last scheduled visit with no subsequent clinical visit). Cox proportional hazards models were used to estimate the association between pre-UTT vs UTT initiation on LTFU by 12 months.Results: We included 2410 patients. A total of 1267 (52.6%) patients initiated ART before UTT implementation and 1143 (47.4%) after the change in policy. LTFU (adjusted Hazard Ratio (aHR): 1.51; 95% Confidence Interval (CI): 1.16– 1.98) between groups and specifically among those initiating with a CD4 cell count ≤ 500 cells/mm 3 (aHR: 1.59; 95% CI: 1.21– 2.10) was higher among patients initiating ART under UTT.Conclusion: LTFU under UTT proved higher than that of previous periods. Patients initiating first-line therapy under the treat-all policy may often start treatment in better health, subsequently not perceiving a direct benefit to treatment which may deter patients from consistent engagement in HIV treatment programmes.Keywords: universal access, antiretroviral therapy, lost to follow-up, virologic suppression, resource-limited settings, South Africa